MON-086 Various Subcutaneous Continuous Glucose Monitors Comparably Lower HbA1c in Children - Gold, Steven (J Endocr Soc, 2020)
Background: Preliminary studies have demonstrated improvement in metabolic control of patients (PTs) using subcutaneous Continuous Glucose Monitoring systems (CGMs). In this study, we investigated the effect of CGMs on PTs’ glycemic control and compared the change in patient HbA1c levels between sensors. Objective: To determine how CGMs affect metabolic control in PTs and the effect of different sensors on glycemic control. Patients and Methods: 33 PTs with Type 1 diabetes mellitus (DM) who began using a CGM between 2017 and 2019 were selected for inclusion. CGM systems used included DexcomG6™, DexcomG5™, DexcomG4™, Enlite™, Guardian 3™, or Medtronic Sure-T™ sensors. Results: The mean (MN) age of PTs at initial visit was 15.3 ± 5.1 yrs and the MN age at second visit was 15.8 ± 5.1 yrs. The MN time between visits was 5.0 ± 2.4 months (mos). 6 PTs had follow up (F/U) times less than 3 mos, 18 PTs had F/U times between 3 and 6 mos, 6 PTs had F/U times between 6 and 9 mos, and 3 PTs had F/U times greater than 9 mos. The MN and median (MD) HbA1c at the initial visit for all PTs was 8.28% ± 1.48 and 8.10%, respectively. The MN and MD HbA1c at final F/U for all PTs was 7.57% ± 1.11 and 7.50%, respectively. The difference in MN HbA1c was significant (p<0.001). The MN and MD HbA1c at the initial visit for PTs with a F/U time less than 3 mos was 7.55% ± 0.77 and 7.75%, respectively. The MN and MD HbA1c at F/U for these PTs was 7.20% ± 0.79 and 7.20%, respectively. The difference in MN HbA1c was significant (p<0.05). The MN and MD HbA1c at the initial visit for all PTs with a F/U time greater than 3 mos was 8.44% ± 1.53 and 8.10%, respectively. The MN and MD HbA1c at F/U for these PTs was 7.66% ± 1.15 and 7.50%, respectively. The difference in MN HbA1c was significant (p<0.001). The MN change of HbA1c between visits was not significant between PTs who had 3–6 mo, 6–9 mo, and 9+ mo F/U times (p=0.96) 15 PTs had HbA1c levels less than or equal to 8.0%. The MN and MD HbA1c at initial visit for these PTs was 7.20% ± 0.41 and 7.30%, respectively. The MN and MD HbA1c at F/U for these PTs was 6.75% ± 0.47 and 6.80%, respectively. The difference in MN HbA1c was significant (p<0.001). 20 PTs had HbA1c levels greater than 8.0% at initial visit. The MN and MD HbA1c at the initial visit for these PTs was 9.18% ± 1.47 and 8.80%, respectively. The MN and MD HbA1c at F/U for these PTs was 8.26% ± 1.03 and 8.00%, respectively. The difference in MN HbA1c was significant (p<0.001). The MN change in HbA1c between the high HbA1c group (-.92% ± 1.02) and low HbA1c group (-0.45% ± 0.32) was not significant (p>0.05). 25 PTs used a Dexcom™ sensor while 8 PTs used a Medtronic™ sensor. The MN change in HbA1c was not significant between these brands (p>0.05). Conclusion: CGMs improve metabolic control in pediatric PTs with Type 1 DM regardless of initial HbA1c. Further, this improved control is sustained over time. Sensor brands appear to be equally effective at achieving this goal.